Screening of molecular markers associated with hornless traits in Qira black sheep - Wen Zhou; Lijun Zhu; Yuwei Peng; Xiaopeng Li; Xuechen Zhang; Zhipeng Han; Jingping Li; Xinyu Bai; Qifeng Gao; Ruizhi Yang; Tao Jiang; Shudong Liu (BMC Genomics)
Abstract Hornless trait in sheep is one of the important traits affecting their economic production efficiency. In order to screen the molecular markers related to hornless trait in Qira black sheep, we used Illumina Ovine 50 K SNP chip data of 189 Qira black sheep, which were divided into two groups based on their horned and hornless traits. GWAS analysis of individuals of interest. Used the horned trait group as the reference group, and performed xp-EHH analysis with the hornless group. The hornless group was subjected to iHS and Pi analyses. After annotating the relevant candidate regions based on the sheep 4.0 genome microarray data. 681 candidate genes were obtained from the xp-EHH analysis, 87 candidate genes from the iHS analysis, and 2,171 candidate genes from the Pi analysis. A total of 19 candidate genes were obtained from further analysis of the candidate regions. Candidate genes were analyzed by GO and KEGG, and RXFP2, TNS3, EYA2 and OCSTAMP genes were found to be associated with horned traits in Qira black sheep. Further PCR validation of RXFP2 revealed that loci 10: 29,501,280 (P = 0.002), 10: 29,501,431 (P = 0.003) and 10: 29,051,333 (P = 0.0001) were significantly associated with hornless trait in Qira black sheep.